'Go hard or go home': a social practice theory approach to young people's 'risky' alcohol consumption practices. Issue 1 (1st January 2021) - Hennell, Kath; Piacentini, Maria; Limmer, Mark
ABSTRACT: Developing a deep and contextualised understanding of risk is important for public health responses to young people's alcohol consumption, which is frequently positioned as an outcome of risky behaviour. This paper expands conceptualisations of risk to encompass its wider social and cultural context through a social practice exploration of young people's controlled and managed intoxicated alcohol consumption practice. We report data from a fourteen-month qualitative study of the alcohol consumption practices of 23 young people in England, drawing on group interviews and social media interactions. Our findings provide a nuanced understanding of risk-taking, demonstrating that risk is an important aspect of the ongoing participation and performance in alcohol consumption practice and that health information and advice can be and was frequently incorporated into drinking practice without contributing to fundamental change. This raises new questions about the effectiveness of health interventions that focus on the individual, discussed in the final section of the paper.